Analysis of Early Assessable Risk Factors for Poor Outcome in Dogs With Cluster Seizures and Status Epilepticus - Cagnotti, Giulia; Ferrini, Sara; Ala, Ugo; Bellino, Claudio; Corona, Cristiano; Dappiano, Elena; Di Muro, Giorgia; Iulini, Barbara; Pepe, Ida; Roncone, Silvia; D'Angelo, Antonio (Frontiers in Veterinary Science, 2020)
Status epileptics (SE) and cluster seizures (CS) are serious neurological emergencies associated with poor outcome in epileptic patients. Data on risk factors associated with outcome in epileptic patients affected by CS and SE have not been studied extensively to date. In the present retrospective study potential risk factors predictive of negative outcome in a population of dogs affected by CS and SE were analyzed. Ninety-three dogs were included in the study: 21/93 patients (23%) presented with SE and 72/93 (77%) with CS. Based on multivariate statistical analysis, factors statistically associated with a poor outcome were the occurrence of the first epileptic seizure outside the defined idiopathic interval (6 months – 6 years), a condition of hyperthermia at presentation and the absence of previous antiepileptic drugs (AEDs) in case of previous history of seizures. The results of the present study implement data on risk factors associated with poor outcome in dogs affected by CS or SE and can aid in the creation of an ad hoc scoring system, similar to systems currently applied in human medicine upon hospital admission to benchmark performances and establish protocols for triage and therapeutic management.